Glucocorticoids and behavior in non-human primates: A meta-analytic approach to unveil potential coping mechanisms - Fiorini-Torrico, Roberto; De Vleeschouwer, Kristel Myriam; Fuzessy, Lisieux [UNESP]; Oliveira, Leonardo de Carvalho (Elsevier, 2024)
Glucocorticoids (GCs) mediate responses to energetic and psychosocial challenges and are associated with behavioral adjustments that form part of an adaptive vertebrate stress response. GCs and behavior can indirectly influence each other, leading to either an intensification or attenuation of stress responses. Exploring these GC-behavior relationships may offer insights into the beneficial aspects of behavior and help identify coping mechanisms that potentially enhance individual fitness. We conducted a systematic review of the relationship between GCs and several behavioral traits, as described in the literature on captive and wild primates, and evaluated the effect of different categorical factors on these relationships using a meta-analytic approach. According to the type of behavior, we grouped statistical measures into affiliative, agonistic, anxiety-like, and foraging domains which were further differentiated into behavioral subgroups. We also categorized measures based on setting, method, sex and age of individuals, and sample matrix involved in each primary study. Overall, we found that some affiliative and foraging behaviors are associated with lower GC levels, while agonistic and anxiety-like behaviors are linked to higher GC levels. Specifically, non-sexual affiliation and energetically inexpensive activities were negatively related to GCs. In contrast, inter- and intragroup aggression, noncommunicative and self-directed behaviors, and energetically expensive activities were positively related to GCs. By demonstrating how certain social, ecological and intrinsic factors affect the GC-behavior relationships, our study helps elucidate the contexts that may alleviate or intensify the stress responses in non-human primates.
Keywords: Behavior; Captive; Coping; Correlations; Cortisol; Meta-analysis; Non-human primates; Stress alleviation; Stress response; Wild